Trauma And Memory: Subaltern Experience In Baburao Bagul’s Streetwalker - Nagendrapramoth S; Dr.K. Thayalamurthy (Revista Electronica de Veterinaria, 2024)
Trauma is a deeply distressing or disturbing experience that overwhelms an individual’s ability to cope, often causing lasting emotional, psychological, or physical effects. Memory is the ability to store, retain, and recall information, experiences, and knowledge over time. This article explores the complex interplay of trauma and memory within the framework of subaltern experiences, through the short story Streetwalker as a contextual analysis. Girja, the protagonist, embodies the dual burden of systemic oppression and personal grief as she navigates life as a marginalized sex worker. Drawing on trauma theory, particularly the works of Cathy Caruth and Dominick LaCapra, this paper explores how Girja’s traumatic experiences and memories are inscribed on her body and psyche, creating a cycle of pain and resilience. The narrative captures the fragmentation and repetition characteristic of traumatic memory, highlighting the ways in which Girja’s maternal love and memories of her son both fuel her endurance and deepen her anguish. Girja’s story highlights the intersection of personal and structural violence, reflecting the voicelessness and invisibility imposed upon subaltern subjects while also revealing moments of resistance and agency. Analysing the representation of trauma as both a psychological phenomenon and a socio-political construct, this article situates Streetwalker within broader discussions of power, memory, and resilience in subaltern studies. It argues that the narrative foregrounds the enduring human spirit in the face of systemic erasure and trauma, emphasizing memory as both a source of suffering and a vehicle for subaltern resistance.